Eugenol em juvenis de tilápia do nilo: Concentrações e administrações sucessivas - Delbon, Marina Carvalho [UNESP] (2012)
Several anesthetics are used in aquaculture to reduce the stress caused by management. In the field, the most common anesthetic is benzocaine, but several authors are researching about eugenol. The objective of this study were to compare the action of these drugs on the anesthetics stages and measure the effects of successive administration of eugenol on the anesthetics stages in Oreochromis niloticus. In the first test, fish (47.73 ± 8.73 g and 14.23 ± 0.81 cm) were subjected to five concentrations of eugenol (40, 60, 80, 100 and 120 mg L-1) and one of benzocaine (100 mg L-1). All the anesthetic concentrations tested were able to induce fish to all stages of anesthesia, and revealed an inverse relationship between the induction times and increased concentrations. The minimum concentration of eugenol to induce anesthesia was 100 mg L-1. In the second test, the juveniles (38.07 ± 5.00 g and 12.70 ± 0.54 cm) were exposed to concentrations of 60, 80, 100 mg L-1 of eugenol, as determined in the first test. Evaluating the differences between successive days, there was no significant difference (P>0.05) between anesthetics stages in the concentrations of eugenol tested, suggesting that the residue of eugenol was removed from the fish in less than 24 hours.